2016
DOI: 10.7717/peerj.2707
|View full text |Cite
|
Sign up to set email alerts
|

Dominance relationships in a family pack of captive arctic wolves (Canis lupus arctos): the influence of competition for food, age and sex

Abstract: BackgroundDominance is one of the most pervasive concepts in the study of wolf social behaviour but recently its validity has been questioned. For some authors, the bonds between members of wolf families are better described as parent-offspring relationships and the concept of dominance should be used just to evaluate the social dynamics of non-familial captive pack members (e.g., Mech & Cluff, 2010). However, there is a dearth of studies investigating dominance relationships and its correlates in wolf family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 46 publications
(89 reference statements)
2
19
0
Order By: Relevance
“…Older dogs were more likely to be classified as dominant than younger dogs, in agreement with the literature for both wolves and dogs [22,23,46,47,79]. One-year old dogs had a 50% probability of being classified as dominant, which seems high given their age and amount of experience.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Older dogs were more likely to be classified as dominant than younger dogs, in agreement with the literature for both wolves and dogs [22,23,46,47,79]. One-year old dogs had a 50% probability of being classified as dominant, which seems high given their age and amount of experience.…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, the relationships tend to be less strong in larger dog packs and to be more specifically related to the formal dominance style [26,27,45]. Age, sex, leadership and reproductive success have also been found to be related to dominance status in free ranging and/or pet dogs [24,26,[46][47][48][49]. Theoretical models predict that intra-specific dominance, especially when tied to consistent leadership, is only useful in small groups characterized by asymmetric distribution of experience and familiarity with the environment [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…In one study on free-ranging dogs, a sex age graded hierarchy was found, such that males dominate females in each age class, and adults dominate over subadults, and subadults over juveniles . However, sex had no clear effect on dominance in a family pack of captive arctic wolves, although sex-separated linear hierarchies showed a stronger linearity than female-male hierarchies (Cafazzo, Lazzaroni & Marshall-Pescini, 2016). Personality traits might also associate with dominance status.…”
Section: Dominance In Dogs As Rated By Owners Corresponds To Ethologimentioning
confidence: 85%
“…Studies in wild and captive wolves disagree on what should be considered the natural social and hierarchical structure. While captive wolves and domestic dogs showed heightened agonistic behaviour and a social structure best described by a linear hierarchical model (Cafazzo, Lazzaroni, & Marshall-Pescini, 2016;Cafazzo, Valsecchi, Bonanni, & Natoli, 2010), wild wolves have been described as living in family units, consisting of a breeding pair with their offspring (Gadbois, 2004;Mech, 1999;Packard, 2003). Family compositions suggest a non-linear and more complex but, at the same time, more flexible hierarchical structure (Packard, 2003) with the parents playing the roles of leaders, making group decisions and initiating group movements (Peterson, Jacobs, Drummer, Mech, & Smith, 2002).…”
Section: Evolution Of Social Structurementioning
confidence: 99%